“It's the patient that suffers from poor communication”: Analyzing communication gaps and associated consequences in handover events from nurses’ experiences - Roger A. Atinga; Mtebi Nkrabia Gmaligan; Alice Ayawine; John K. Yambah (SSM: Qualitative Research in Health)
Background: Although routine communication gaps among clinical shift teams significantly account for adverse care and treatment outcomes, existing analysis of the phenomenon remain limited in low middle income countries battling with patient safety issues. This study analyzed the drivers and associated episodic consequences of communication gaps from nurses’ experiences in Ghana. Methods: Qualitative design implemented in two referral hospitals. Data collection involved site observations and in-depth interviews with general nurses, midwives, and staff nurses across 3-cycle shift regimes in the emergency, ICU, inpatient wards, and maternity units. A two-stage data analysis was adopted by integrating deductive and inductive codes into broad thematic typologies explaining drivers of communication gaps and the consequences thereof. Results: Communication gaps among shift teams were largely driven by a combination of three broad factors: a) Attitudinal elements of poor work ethics, poor documentation, interpersonal conflicts and use of unconventional language that impaired effective communication; b) organizational dynamics of taxing job demands, limited training exposure and lack of formal handover communication procedures which allowed shift teams to adopt default patterns of communication behavior; and c) cultural values, stereotyping and prejudicing behaviors that restricted inclusive interactions among shift teams. These communication gaps produced adverse episodic effects of diagnostic and treatment errors, complications, and extended hospitalizations. Conclusion: The findings underscore the need to develop standard guidelines to direct structured communication alongside equipping shift teams with competences on emotional intelligence to overcome cultural and behavioral adversities that influence communication breakdown.